Implementation of 5M Strategy in Distance Learning of English Language Teaching (ELT) - Madya Giri Aditama; Prasetyawan Aji Sugiharto (STAI Miftahul Ula Nganjuk, 2021)
English Language Teaching (ELT) in Indonesia faced crucial time during Covid-19 pandemic period. In the distance learning process of ELT, teachers face difficulties in doing teaching learning process. 5M strategy helped teachers to maximize their relationship with students and parents in order to create an essential teaching learning activity, the objectives of this study are “Classifying the 5M strategy applied by the teacher in Distance Learning of ELT” and “Describing the example method of each strategy used by teacher in Distance Learning of ELT process”. The study employed qualitative approach in which the researchers used questionnaire and interview to collect the data. The participants were 20 high school English teachers in Batang region. From the study, it was found that the teachers applied 5M strategy in their learning process. The resuls shown that there are 16 teachers (80%) applied Memanusiakan Hubungan (Humanize Relationships) strategy, only 8 teachers (40%) applied Memahami Konsep (Understanding Concepts) strategy, 16 teachers (80%) considered Membangun Keberlanjutan (Building Sustainability) strategy in their teaching, 17 teachers (85%) presented Memilih Tantangan (Choosing Challenges strategy, and all 20 teachers (100%) were able to apply Memberdayakan Konteks (Empowering Context) strategy. This study also reveals some unique and new teaching methods applied in each strategy by the teachers.